Standardization and Adaptation of International Franchising in Morocco: The case of fast food franchises - SAYL, ZINEB (Archives of Business Research, 2022)
This article aims to analyze the appropriate level of standardization and adaptation that has determined the success of international franchising in Moroccan market. We propose a comparative study between two American fast food franchises: McDonald’s and Subway. The success of McDonald’s franchise and the failure of Subway franchise in Moroccan market, suppose that there are key factors to entry in this market. We therefore present a managerial and marketing analyze of each case to determine the appropriate level of standardization and adaptation. The results indicate that the international franchise system maintains a high level of the standardization of the business package, it is also evident to modify the methods of operations and marketing mix strategy to adapting their products to specific behavior of the Moroccan consumer. Moreover, the results suggest that the McDonald’s franchise adapts a higher level of adaptation than the subway to entry Morocco.